2007
DOI: 10.1590/s0102-261x2007000600016
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial F-region irregularities generated by the Rayleigh-Taylor instability mechanism: rocket observations from Brazil

Abstract: ABSTRACT. Several sounding rockets carrying plasma diagnostic experiments were launched from the Brazilian rocket launching stations in Natal (5.9 • S, 35.2 • W Geog. Lat.) and Alcântara (2.31 • S, 44.4 • W Geog. Lat.). Langmuir Probes (LP) were used to measure the height profiles of electron density and electron temperature and High Frequency Capacitance (HFC) probes were used to measure electron density. The LP's were also used to measure the amplitude of electron density fluctuations.A detailed study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…On the other hand, several plasma bubbles of mediumlarge scale were observed in the downleg profile (descent of the rocket), around the base of F region and also topside of it, but without any sharp indication of the F region base from an altitude above 240 km. The rocket traversed through regions of different altitudes separated by a few hundred kilometers during upleg and downleg, so this might elucidate the large differences observed in ascent and descent of the rocket (Muralikrishna et al, 2003;Muralikrishna and Abdu, 2006;Muralikrishna and Vieira, 2007). A detailed explanation of in situ experiment and the analysis is found in Muralikrishna et al (2003), Muralikrishna and Abdu (2006), and Muralikrishna and Vieira (2007).…”
Section: In Situ Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, several plasma bubbles of mediumlarge scale were observed in the downleg profile (descent of the rocket), around the base of F region and also topside of it, but without any sharp indication of the F region base from an altitude above 240 km. The rocket traversed through regions of different altitudes separated by a few hundred kilometers during upleg and downleg, so this might elucidate the large differences observed in ascent and descent of the rocket (Muralikrishna et al, 2003;Muralikrishna and Abdu, 2006;Muralikrishna and Vieira, 2007). A detailed explanation of in situ experiment and the analysis is found in Muralikrishna et al (2003), Muralikrishna and Abdu (2006), and Muralikrishna and Vieira (2007).…”
Section: In Situ Experimentsmentioning
confidence: 99%
“…Some of the key results from the aforementioned (Muralikrishna et al, 2003;Muralikrishna and Abdu, 2006;Muralikrishna and Vieira, 2007) analyses indicate (1) the initiation of a cascade process, owing to the generalized Rayleigh-Taylor instability mechanism near the base of F region that resulted in the development of plasma bubbles or large-scale irregularities, and (2) subsequently, when energy was advected to higher altitudes, smaller-scale irregularities were observed, owing to the cross-field instability mechanism.…”
Section: In Situ Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been established that the seeding by these waves becomes pertinent in the solstice months, when the post sunset rise (PSSR) of the F layer is weak (Tsunoda, 2010a). Muralikrishna and Vieira (2007) reported that a higher F region base is preferable for R-T instability to operate. Ossakow et al (1978) presented a numerical simulation study, showing that the injection of an artificial depletion at the bottom side of the F layer can cause ESF to occur.…”
Section: Introductionmentioning
confidence: 99%